The art and science of sociology : essays in honour of Edward A. Tiryakian - Robertson, Roland; Simpson, John Herman, 1936-; Tiryakian, Edward A. (London : Anthem Press, 2016)
The book consists of a volume of essays in honor of the outstanding sociologist, Edward A. Tiryakian; whose work has spanned a considerable number of countries, regions and topics. He has been highly influential, particularly in American and French sociology. The contributors include such luminaries as Alan Sica, Bryan Turner, George Ritzer, John Simpson, Piotr Sztompka, Hans Joas, Roland Robertson and John Torpey.
Title from publisher's bibliographic system (viewed on 11 Aug 2017).
Keywords: Sociology